Performance, cost, and ecological assessment of fiber-reinforced high-performance mortar incorporating pumice powder and ground granulated blast furnace slag as partial cement replacement - Ifzaznah, Husayn Hasan Husayn; Gullu, Ahmet; Memis, Selcuk; Yaprak, Hasbi; Gençel, Osman; Ozbakkaloglu, Togay; Gençel, Osman (Elsevier Sci Ltd, 2024)
The production of cement and concrete is a significant source of greenhouse gas emissions. Hence, recent governmental regulations have brought the attention of industry and academia to the environmental impact of these materials. Recognizing the pressing need to address the environmental footprint of the widely used construction materials, there is a growing focus on strategic initiatives that involve incorporating alternative waste materials to partially substitute ordinary Portland cement (OPC). It is also noteworthy that high-performance concrete and mortar emits significantly less CO2 per unit of strength. Therefore, this study aims to develop high-strength mortar mixes incorporating pumice powder (PP) and ground granulated blast-furnace slag (GGBS) as substitutes for OPC. To this end, nine different mixes, with varying levels of OPC replacement ranging from 0% to 60%, were produced. These mixes underwent a comprehensive experimental evaluation to assess their physical, mechanical, and durability properties. Scanning electron microscopy analyses were conducted to examine the microstructural characteristics of the mixes as well. Furthermore, the embodied energy, embodied carbon, and cost of the prepared mixes were calculated. The experimental findings suggest that high-strength mortar, with a compressive strength varying between 64 and 82 MPa at 28 days of curing, can be successfully produced with reduced embodied carbon and embodied energy compared to conventional mortar mix while maintaining a comparable cost.
Keywords: Cleaner Production; Ecological Assessment; Cement Replacement; Waste Material; Pumice; Ground Granulated Blast Furnace Slag